Outlook for clean air in the context of sustainable development goals. (November 2018) - Rafaj, Peter; Kiesewetter, Gregor; Gül, Timur; Schöpp, Wolfgang; Cofala, Janusz; Klimont, Zbigniew; Purohit, Pallav; Heyes, Chris; Amann, Markus; Borken-Kleefeld, Jens; Cozzi, Laura
Graphical abstract: Change in concentrations of PM2.5 in China by scenario. Highlights: Under current policies the air pollution related SDGs will likely not be met. Integrated policies to achieve energy access, climate and air quality goals are examined. Multiple SDGs can be attained simultaneously with substantial co-benefits. Additional cost are modest against major societal gains. Abstract: Air pollution is linked with many of the United Nations Sustainable Development Goals. Strategies aiming at the improved air quality interact directly with climate mitigation targets, access to clean energy services, waste management, and other aspects of socio-economic development. Continuation of current policies in the key emitting sectors implies that a number of sustainability goals will likely not be met within the next two decades: emissions of air pollutants would cause 40% more premature deaths from outdoor air pollution than today, carbon emissions would rise globally by 0.4% per year, while nearly two billion people would not have access to clean cooking. This paper examines integrated policies to put the world on track towards three interlinked goals of achieving universal energy access, limiting climate change and reducing air pollution. Scenario analysis suggests that these goals can be attained simultaneously with substantial benefits. By 2040, emissions of main pollutants are projected to drop by 60–80% relative to today, and associated health impacts are quantified at two million avoided deaths from ambient and household air pollution combined. In comparison to costs needed for the decarbonization of global economy, additional investments in air pollution control and access to clean fuels are very modest against major societal gains. However, holistic and systemic policy assessment is required to avoid potential trade-offs.